Phage Resistance Reduced the Pathogenicity of Xanthomonas oryzae pv. oryzae on Rice - Mengju Liu; Ye Tian; Haitham E. M. Zaki; Temoor Ahmed; Rong Yao; Chengqi Yan; Sebastian Leptihn; Belinda Loh; Muhammad Shafiq Shahid; Fang Wang; Jianping Chen; Bin Li (Viruses, 2022)
Plants grow together with microbes that have both negative and positive impacts on the host, while prokaryotes are in turn also hosts for viruses, co-evolving together in a complex interrelationship. Most research focuses on the interaction of either bacterial pathogens interacting with the plant host, or the impact on viruses on their pathogenic bacterial hosts. Few studies have investigated the co-evolution of bacterial pathogens with their host plants as well as with their bacterial viruses. In this work, we aimed to identify the genes that were associated with both phage sensitivity and host pathogenicity of the bacterium Xanthomonas oryzae pv. oryzae (Xoo), which is the most important bacterial rice pathogen. Using the Tn5 transposon mutation technology, we created a library of Xoo strain C2 comprising 4524 mutants, which were subsequently tested for phage infectability. The phage infection tests showed that less than 1% of the mutants (n = 36) were resistant to phage infection, which was attributed to the Tn5 insertion in 19 genes. Interestingly, three out of 19 genes that conveyed resistance to the phage resulted in reduced pathogenicity to rice seedlings compared to the wild type. We identified three genes involved in both phage infection and bacterial virulence, which were studied by knockout mutants and complementation experiments. All of the three knockout mutants were resistant to infection by phage X2, while the complemented strains restored the susceptibility to the bacterial virus. Surprisingly, the genes are also essential for pathogenicity, which we confirmed by single knockout mutants corresponding to the Tn5 mutants. All three genes are involved in lipopolysaccharide synthesis, thus changing the cell envelope surface molecule composition. Our work shows a possible balance in terms of the connection between bacterial virulence and phage resistance, supporting the deployment of phages for the biocontrol of plant pathogens.